Purification and Characterization of Glucose Oxidase of Aspergillus niger IPBCC.08.610 - ANINDA INDRIANI; LAKSMI AMBARSARI; DEWI SESWITA ZILDA (Microbiology Indonesia, 2018)
Glucose oxidase was an enzyme which catalyzed Î²-D-Glucose to gluconic acid and hydrogen peroxide. Glucose oxidase from Aspergillus niger IPBCC.08.610 was isolated, purified and characterized. The enzyme was purified by ammonium sulphate precipitation and dialysis. The specific activity and yield of dialysis fraction were 19.766 U/mg and 4.744%. The optimum pH and temperature were 6 and 30oC. The stability of enzyme at optimum pH and temperature was decreasing 50% at 25 minutes. The km and vmax values for enzyme were 27 mM and 0.986 U/mg.